Method for producing zirconia sintered body

By applying a controlled alternating current electric field and managing current increase for constant shrinkage, the method enhances zirconia sintered body density and grain size uniformity, overcoming limitations of conventional flash sintering.

JP7599650B2Active Publication Date: 2024-12-16NAT UNIV CORP TOKAI NAT HIGHER EDUCATION & RES SYST +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021000439
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-05
Publication Date
2024-12-16
Estimated Expiration
2041-01-05

AI Technical Summary

Technical Problem

Conventional flash sintering methods for zirconia require high applied voltages and do not achieve the desired high sintered body density.

Method used

A manufacturing method involving a controlled alternating current electric field of 30 V/cm to 60 V/cm, with a current increase step to maintain a constant shrinkage rate, to produce a zirconia sintered body at lower temperatures and voltages.

Benefits of technology

The method achieves a zirconia sintered body with higher density and controlled grain size, outperforming conventional methods by ensuring densification and uniformity.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide a method of producing sintered zirconia of a higher sintered density by flash sintering, applying a low application voltage, as opposed to conventional flash sintering, applying a high application voltage.SOLUTION: The method of producing sintered zirconia includes: a temperature raising step (A) of raising a temperature of a molded article to a temperature (Ta) at which a flush phenomenon can occur in the molded article while applying an AC electric field of 30 V / cm or more and less than 60 V / cm to the molded article containing zirconia, wherein the temperature of the molded article is raised up to the temperature (Ta) at which a current flowing in the molded article indicates a limit current value (a) set between 2 mA / mm2 or more and 20 mA / mm2 or less; a current increasing step (B) of increasing a current flowing in the molded article up to a current value of a densification current which is the maximum current value flowing in the molded article by the flush phenomenon of the molded article from a current value of a start current which is the limit current value (a) at the temperature (Ta) after the temperature raising step (a), wherein the current flowing in the molded article is increased while controlling the current flowing in the molded article so that a shrinking speed of the molded article is made constant; and a densification step (C) of densifying the molded article by maintaining the molded article at the temperature (Ta) and under a condition in which the current flowing in the molded article indicates the current value of the densification current after the current increasing step (B).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing a zirconia sintered body. [Background technology]

[0002] Flash sintering is a sintering method that utilizes the phenomenon of a sudden increase in current at a specific temperature when an electric field is applied (the so-called flash phenomenon). Compared to conventional sintering methods such as atmospheric sintering and pressure sintering, flash sintering allows sintering to proceed in a shorter time and at a lower temperature, and is therefore attracting attention as a new sintering method for ceramics.

[0003] In Non-Patent Document 1, it is reported that flash sintering occurs when a voltage of 40 V / cm is applied after heating to 1150°C, and that the sintering temperature decreases with increasing applied voltage. In addition, Patent Document 1 reports that densification of zirconia is promoted by applying an electric field after heating to a temperature exceeding the temperature at which the flash phenomenon occurs, and suggests that a sintered body with a relative density of 99% or more can be obtained by heating to 1200°C, applying an AC voltage of 60 V / cm, and sintering for 5 minutes. In addition, Patent Document 1 discloses that if the applied voltage is constant, the flash temperature is uniquely determined and cannot be set arbitrarily. In addition, Non-Patent Document 2 reports that further densification of zirconia is achieved by controlling the shrinkage rate during the flash phenomenon, and that by controlling the shrinkage rate by controlling the current value, a density of 6.01 g / cm can be achieved by sintering at about 800°C for several minutes with an applied voltage of 100 V / cm. 3 It is disclosed that a zirconia sintered body having the above structure can be obtained. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-182689 A [Non-patent literature]

[0005] [Non-Patent Document 1] Rapid Communications of the American Ceramic Society,Vol.93,No.11,(2010)p.3556-3559 [Non-Patent Document 2] Kimihiro Taguchi et al., Proceedings of the Autumn Lecture Meeting of the Japan Society of Powder and Powder Metallurgy, 2-60A (2019) Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present disclosure is to provide a manufacturing method for flash sintering using a low applied voltage, which results in a sintered body having a higher sintered body density than that obtained by conventional flash sintering using a high applied voltage. [Means for solving the problem]

[0007] The present invention is as defined in the claims, and the gist of the present disclosure is as follows.

[0008] [1] A temperature-raising process in which an AC electric field of 30 V / cm or more and less than 60 V / cm is applied to a zirconia-containing molded body, while the temperature of the molded body is raised to a temperature (Ta) at which a flash phenomenon can occur in the molded body, wherein the current flowing through the molded body is 2 mA / mm 2 More than 20mA / mm 2 A temperature increasing step (A) of increasing the temperature of the molded body to the temperature (Ta) that indicates the limiting current value (a) set between: a current increasing step (B) for increasing a current flowing through the compact at the temperature (Ta) after the temperature increasing step (A) from a current value of a start current, which is the limiting current value (a), to a current value of a densification current, which is a maximum current value flowing through the compact due to a flash phenomenon of the compact, and for increasing a current flowing through the compact while controlling a current value flowing through the compact so that a shrinkage rate of the compact is constant; a densification step (C) of densifying the compact by maintaining the compact at the temperature (Ta) and under a condition in which a current flowing through the compact exhibits a current value of the densification current after the current increasing step (B); A method for producing a zirconia sintered body comprising the steps of: [2] The manufacturing method according to [1], wherein in the current increasing step (B), the current flowing through the green body is increased from the current value of the starting current to the current value of the densification current over a period of 5 minutes or more. [3] The current value of the densification current is 80mA / mm 2 The manufacturing method described in [1] or [2] above. [4] The method according to any one of [1] to [3], wherein the temperature (Ta) is 1100° C. or lower. [5] The method according to any one of [1] to [4], wherein the frequency of the AC electric field is 50 Hz or more and 10,000 Hz or less. [6] The method according to any one of [1] to [5], wherein the molded body contains 2 mol % or more and 6 mol % or less of yttria, with the remainder being zirconia. Effect of the Invention

[0009] According to the present disclosure, it is possible to provide a method for producing a zirconia sintered body, which is a method of flash sintering using a low applied voltage and has a higher sintered body density than that achieved by conventional flash sintering using a high applied voltage. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, the method for producing a zirconia sintered body will be described in detail, but the description of the constituent elements described below is an example as one embodiment of the present disclosure, and the present invention is not limited to these contents. In this specification, the terms are defined as follows.

[0011] The "flash phenomenon" is a phenomenon in which current rises suddenly at a specific temperature when a voltage is applied to a green body (compressed powder), and "flash sintering" is a sintering method that densifies a green body (compressed powder) by the flash phenomenon. The "flash temperature" is the temperature at which the flash phenomenon occurs, and is the temperature at which the current value rises suddenly (increases) when the temperature is raised with a voltage applied. An "AC electric field" is an electric field that is generated when an AC voltage is applied to a molded body with electrodes fixed to both ends, and is expressed as applied voltage [V] / electrode distance [cm]. The term "green body" refers to a compact made of powder in which powder particles are agglomerated by physical force to maintain a certain shape.

[0012] Hereinafter, the method for producing a zirconia sintered body according to the present disclosure will be described with reference to an example of an embodiment. In this embodiment, A temperature-raising process in which an AC electric field of 30 V / cm or more and less than 60 V / cm is applied to a zirconia-containing compact to raise the temperature of the compact to a temperature (Ta) at which a flash phenomenon can occur in the compact, wherein the current flowing through the compact is 2 mA / mm 2 More than 20mA / mm 2 A temperature increasing step (A) of increasing the temperature of the molded body to the temperature (Ta) that indicates the limiting current value (a) set between: a current increasing step (B) which is a step of increasing a current flowing through the compact at the temperature (Ta) after the temperature increasing step (A) from a current value of a start current, which is the limiting current value (a), to a current value of a densification current, which is a maximum current value flowing through the compact due to a flash phenomenon of the compact, and which increases the current flowing through the compact while controlling the current value flowing through the compact so that the shrinkage rate of the compact is constant; a densification step (C) of densifying the compact by maintaining the compact at the temperature (Ta) and under conditions in which the current flowing through the compact exhibits the current value of the densification current after the current increasing step (B); A method for producing a zirconia sintered body, comprising the steps of: In the manufacturing method of this embodiment, by controlling the degree of increase in the current flowing through the molded body due to the flash phenomenon, a dense zirconia sintered body can be obtained at a lower temperature, despite the applied voltage being lower than conventionally.

[0013] <Molded body> The molded body used in the manufacturing method of this embodiment is a molded body containing zirconia, and may be a compact mainly made of zirconia. The zirconia is preferably partially stabilized zirconia, and more preferably partially stabilized zirconia containing yttria. In a molded body made of zirconia containing yttria, the content of yttria relative to zirconia (also referred to as "yttria content") is preferably 2 mol% or more or 3 mol% or more, and preferably 6 mol% or less or 5 mol% or less. For example, the molded body used in the manufacturing method of this embodiment preferably contains 2 mol% or more and 6 mol% or less of yttria, with the remainder being zirconia. Here, the "yttria content" refers to the molar ratio of yttria to the total of zirconia (ZrO2) and yttria (Y2O3), and can be calculated by (Y2O3 / (ZrO2+Y2O3)×100 [mol %]). The shape of the molded body is arbitrary, and may be disk-like, cylindrical, cubic, rectangular, polygonal, approximately polygonal, spherical, approximately spherical, or any other shape depending on the application. The size of the molded body may be any size so long as a voltage can be applied uniformly. For example, in the case of a cubic molded body, the length of one side can be 2 mm or more and 200 mm or less. Next, each step in the method for producing the zirconia sintered body of the present disclosure will be described.

[0014] <Temperature increasing process (A)> The temperature-raising step (A) according to the present disclosure is a step of raising the temperature of a zirconia-containing compact to a temperature (Ta) at which a flash phenomenon can occur in the compact while applying an AC electric field of 30 V / cm or more and less than 60 V / cm to the compact, and the current flowing in the compact is 2 mA / mm 2More than 20mA / mm 2 This is a process of increasing the temperature of the compact to a temperature (Ta) at which the limiting current value (a) set during the following period.

[0015] In the temperature increasing step, an AC electric field of 30 V / cm or more and less than 60 V / cm is applied to the compact. Here, the electric field value (effective value) of the AC electric field is 30 V / cm or more and less than 60 V / cm, preferably 35 V / cm or more or 40 V / cm or more, and preferably 55 V / cm or less or 50 V / cm or less. By raising the temperature while applying an AC electric field to the molded body, the start of the flash phenomenon can be captured. Since a reduced region is unlikely to occur inside the sintered body, the frequency of the AC electric field is preferably 50 Hz or more, or 75 Hz or more, and is preferably 10,000 Hz or less, 5,000 Hz or less, or 2,000 Hz or less. In the temperature increasing step, the temperature of the compact is increased to a temperature (Ta) at which a flash phenomenon can occur. In this specification, "temperature" means the temperature of the molded body, and this temperature of the molded body can be determined by measuring the temperature inside the device in which the molded body is heated. As in the case of commonly used temperature monitors for electric furnaces, the temperature of the molded body is detected by a thermocouple of a differential dilatometer, for example, and is displayed on a display as the electric furnace temperature.

[0016] In the temperature raising step, the current flowing through the compact (hereinafter also referred to as "energizing current") was 2 mA / mm 2 More than 20mA / mm 2 Less than 4mA / mm 2 More than 16mA / mm 2 The molded body is heated to a temperature (Ta) at which the limiting current value (a) set within the following range is exhibited. Because the flash phenomenon causes a sudden increase in the current, by artificially suppressing the current flow by setting a limiting current value (a), it is possible to raise the temperature without passing excessive current.

[0017] In the heating process, the heating rate at which the molded body is heated is not particularly limited and can be any rate set as appropriate, but examples of the heating rate include a heating rate of 10°C / min or more or 25°C / min or more and 100°C / min or less or 75°C / min or less. In the temperature increasing step, it is preferable to increase the temperature of the compact until the energizing current flowing through the compact indicates a limiting current value. In this embodiment, the "limited current value" refers to a current value of the energizing current that is set as an upper limit of the current value so that the current flowing through the molded body does not exceed this current value. The value of the current flowing through the molded body can be controlled by setting a limiting current value and controlling the current. The current can be limited by mechanically controlling the current with a power source, for example, using a commercially available power source device (POPF-300-4 manufactured by Matsusada Precision Co., Ltd.). For example, in the temperature rise process, the limiting current value (a) is set to 8 mA / mm 2 In this case, the current flowing through the compact is 8mA / mm 2 The temperature of the compact is raised until it shows

[0018] <Current Increasing Process (B)> The current increasing step (B) according to the present disclosure is a step of increasing the current flowing through the molded body at a temperature (Ta) after the temperature increasing step (A) from the current value of the starting current, which is the limiting current value (a), to the current value of the densification current, which is the maximum current value flowing through the molded body due to the flash phenomenon of the molded body, and is a step (B) of increasing the current flowing through the molded body while controlling the current value flowing through the molded body so that the shrinkage rate of the molded body is constant.

[0019] In the current increasing step, while maintaining the temperature (Ta), the current is increased to reach the densification current while manipulating the limiting current value so that the sintering rate of zirconia (also called the densification rate of zirconia or the contraction rate of zirconia) becomes constant. In the current increasing step, the current flowing through the compact is controlled, so that the flash sintering can proceed more efficiently, resulting in a more dense compact than conventional flash sintering.

[0020] In the current increasing step, the energizing current is increased while controlling the degree of increase (increase) of the energizing current. More specifically, the following operation is carried out as a more preferred embodiment of the current increasing step of the present disclosure. For example, the limiting current is increased while controlling the "shrinkage rate" of zirconia. In the differential thermal dilatometer, a graph (=shrinkage curve) with the horizontal axis being time and the vertical axis being the amount of shrinkage is displayed in real time, and the limiting current is increased so that the slope of the shrinkage curve becomes constant. This makes it possible to increase the current while controlling the degree of increase (increase) of the current. In this way, by increasing the current value according to the shrinkage rate (shrinkage rate) measured by the differential thermal dilatometer, sintering can be performed while preventing the rapid progress of sintering due to a rapid increase in current, and therefore a zirconia sintered body in a better densified state can be obtained. In addition, when the degree (slope) of increase (increase) of the energizing current is steep, it is preferable to set the upper limit of the limiting current to a low value. For example, a few mA / mm 2 It is preferable to set the limit current value so that it increases gradually.

[0021] The difference between the current value at the end of the heating step (corresponding to the current value at the start of the current increase step) and the current value in the next densification step (corresponding to the current value at the end of the current increase step) is, for example, 1.0 A / mm 2 More preferably, it is equal to or greater than this. In this specification, the current applied at the start of the current increasing step is also referred to as the start current, and the current applied at the end of the current increasing step is also referred to as the densification current. The current value of the starting current corresponds to the current value (limiting current value (a)) of the current flowing at the end of the heating process. After the current flowing reaches the limiting current value (a) during the heating process, the process switches to the current increasing process, and while maintaining the molded body at the temperature (Ta) at which the limiting current value (a) was reached, the amount of current is increased (raised) while controlling the amount of current flowing through the molded body. The current value of the densification current should be the maximum value of the current flowing through the compact during the flash phenomenon, and should be 80 mA / mm 2 More than 120mA / mm2 Less than or equal to 100mA / mm 2 The following is acceptable. The increasing behavior of the energizing current in the current increasing step may be either a continuous increase or a discontinuous increase, but it is preferable to increase the energizing current so that the densification speed of the compact is constant. For example, it is preferable to increase the energizing current from the energizing current flowing through the compact at the start of the current increasing step (starting current) to the energizing current flowing through the compact at the end of the current increasing step (densification current) in 5 minutes or more or 10 minutes or more and 30 minutes or less or 20 minutes or less.

[0022] For example, in the current increase step, the limit current value (a) is 8 mA / mm 2 From the current value of the initial current, which is the maximum current value flowing through the compact due to the flash phenomenon of the compact, the current value of the densification current, which is 96 mA / mm 2 The current flowing through the compact is increased while controlling the value of the current flowing through the compact so that the shrinkage rate of the compact remains constant until the shrinkage rate reaches a constant value.

[0023] <Densification process (C)> The densification step according to the present disclosure is a step of densifying the compact by holding the compact under conditions indicating the temperature (Ta) and the current value of the densification current.

[0024] In the densification step, in order to densify the compact, it is advisable to maintain the state at the end of the current increasing step, i.e., to maintain the compact under the same conditions as at the end of the current increasing step, i.e., the temperature (Ta) and the current value of the densification current. The holding time is, for example, 1 minute or more, or 3 minutes or more, and 10 minutes or less, or 8 minutes or less. However, the densification step may have a short holding time of less than 1 minute. In the case of such a short holding time, the densification step may be performed together with the current increase step just before the end of the current increase step, and in such a case, the current increase step may be regarded as a single step consisting of the current increase step and the densification step. By undergoing the above densification step, a molded body (sintered body) in a well-densified state can be obtained.

[0025] The method for producing a zirconia sintered body according to the present disclosure is characterized in that the shrinkage rate of the zirconia molded body is adjusted to a constant value by controlling the current increase (increase) rate from the starting current to the densification current, particularly in the current increasing step (B). This makes it possible to obtain a molded body (sintered body) in a good densified state.

[0026] <Zirconia sintered body> The zirconia sintered body obtained by the manufacturing method of this embodiment may have the same composition as the molded body, and is preferably partially stabilized zirconia, and further preferably partially stabilized zirconia containing yttria. The zirconia sintered body preferably has an yttria content of 2 mol% or more or 3 mol% or more, and preferably has an yttria content of 6 mol% or less or 5 mol% or less.

[0027] The relative density of the zirconia sintered body obtained by the manufacturing method of this embodiment is preferably 98.9% or more, or 99.2% or more, and 100% or less. Here, the term "relative density" refers to the ratio (%) expressed as (ρ / ρ0)×100 of the actually measured density ρ to the theoretical density in this embodiment, that is, the theoretical density ρ0 of zirconia containing yttria calculated by the following formulas (1) to (4). A = 0.5080 + 0.06980X / (100 + X) (1) C=0.5195-0.06180X / (100+X) (2) ρZ=[124.25(100-X)+225.81X] / [150.5(100+X)A2C] (3) ρ0=100 / ρZ (4) (In the above formulas (1) to (4), X is the yttria content (mol %). In addition, in the above formula (3), A2C means A×2×C.) The above "measured density" refers to the ratio of the mass measured by mass measurement to the volume determined by dimensional measurement for a molded product (g / cm 3 ) and for sintered bodies, the ratio of the mass measured by mass measurement to the volume measured by Archimedes' method (g / cm 3 ).

[0028] The average crystal grain size of the zirconia sintered body obtained by the manufacturing method of this embodiment is preferably 400 nm or more and 1000 nm or less. The average crystal grain size of the zirconia sintered body is preferably the value at the surface of the sintered body, and the crystal grain size is preferably uniform, and the difference in average crystal grain size between the vicinity of the outer surface and the vicinity of the center is more preferably 0 nm or more and 100 nm or less. Here, the "average crystal grain size" refers to the average value of 30 crystal grain sizes obtained by using an SEM image of a sintered body obtained by scanning electron microscope observation. Each crystal grain size can be measured by breaking the sintered body by applying a load and measuring the crystal grains observed on the fracture surface exposed by the breakage. The "difference in average crystal grain size between near the outer surface and near the center" refers to the difference in average crystal grain size between near the outer surface of the sintered body and near the center of the sintered body, where "near the outer surface" refers to the region from 0.1 mm to 0.5 mm from the outer surface of the sintered body, and "near the center" refers to the region 1 mm deep at the center of the sintered body in the vertical and horizontal directions. EXAMPLES

[0029] The present embodiment will be described below with reference to examples, but the present embodiment is not limited to the following examples.

[0030] (Relative Density) The actual density of the sample was measured by the Archimedes method. Prior to the measurement, the mass of the sintered body after drying was measured, and then the sintered body was placed in water and boiled for 1 hour as a pretreatment. The theoretical density was calculated using the above formulas (1) to (4), and the relative density (%) was calculated from the value of the actually measured density relative to the theoretical density.

[0031] (SEM observation) A general scanning electron microscope (device name: S3000, manufactured by Hitachi High-Tech Corporation) was used to obtain SEM observation images of the fracture surfaces of the sintered samples. The SEM observation conditions were as follows: Accelerating voltage: 20kV Magnification: 10,000x From the obtained SEM observation, the particle sizes of 30 crystal particles were measured and the average was calculated to obtain the average crystal grain size. Prior to SEM observation, the fracture surface of the sintered body sample was polished to a mirror surface (Ra≦0.02μm) and then pretreated by thermal etching.

[0032] (Linear shrinkage rate) The shrinkage behavior of the sample was observed before heating and after sintering using a differential thermal dilatometer (device name: Thermo plus EV O2TMA8301, manufactured by Rigaku Corporation). During heating, the linear shrinkage rate was calculated from the change in the amount of shrinkage calculated from the following formula (i) in the range of ±5,000 μm. Linear shrinkage rate (% / min) = {(L-△L) / L} x 100 (i) (In the above formula (i), L is the initial green compact length, and ΔL is the contracted length.)

[0033] Example 1 Zirconia powder containing 3 mol% yttria (product name: TZ-3Y, manufactured by Tosoh Corporation) was subjected to uniaxial pressure of 70 MPa and CIP treatment at 100 MPa to obtain a rectangular solid having dimensions of 3.5 mm length x 3.5 mm width x 15 mm length. Platinum paste electrodes were attached to both longitudinal end faces (3.5 mm × 3.5 mm faces) of the compact. The electrodes of the compact were connected to an AC power source, which was then placed in a differential thermal dilatometer (device name: Thermo plus EV O2TMA8301, manufactured by Rigaku Corporation), and the compact was heated from room temperature under the following conditions. Applied voltage: 40V / cm Frequency: 100Hz Heating rate: 50℃ / min

[0034] Current limit: 8mA / mm 2 The temperature of the compact was then raised to 8 mA / mm. 2 The temperature of the molded body was raised to a temperature (1,020° C.) (heating step (A)). Next, while maintaining the temperature at 1020°C, the current was increased to 8 mA / mm 2 (Start current value) to 96mA / mm 2The current was increased to (the densification current value) while carefully setting the limiting current value so that the shrinkage rate of the green body was constant, and the degree of increase (increase) of the energized current was adjusted, and the current was increased from the starting current value to the densification current value over a period of 16 minutes (current increasing step (B)). Next, the temperature was increased to 1020°C and the current to 96mA / mm 2 The green body was held at this temperature for 5 minutes to densify the green body (densification step (C)). The zirconia sintered body of Example 1 was obtained through the above-mentioned temperature increasing step (A), current increasing step (B), and densifying step (C).

[0035] The zirconia sintered body of this example had a relative density of 99.5%, and the average crystal grain size near the surface and near the center of the sintered body was both 0.6 μm, and the crystal grains on the surface and in the center were similar. The linear shrinkage rate in this example was 1.4 (% / min).

[0036] Example 2 In Example 1, the applied voltage during the temperature increasing step (A) was 50 V / cm, and the applied current was 8 mA / mm 2 The temperature-raising step was terminated at the temperature (900°C) at which the temperature reached 900°C, and the current-increasing step (B) and the densification step (C) were carried out while maintaining the temperature (900°C). Except for this, the zirconia sintered body was produced under the same conditions as in Example 1, and the zirconia sintered body of Example 2 was obtained. The relative density of the zirconia sintered body of this example was 99.3%, and the average crystal grain size near the surface and near the center of the sintered body was 0.87 μm. The linear shrinkage rate in this example was 1.3 (% / min).

[0037] Comparative Example 1 In Example 1, the applied voltage during the temperature increasing step (A) was 100 V / cm, and the applied current was 8 mA / mm 2The temperature-raising step was terminated at the temperature (780°C) at which the temperature reached 780°C, and the current-increasing step (B) and the densification step (C) were carried out while maintaining the temperature (780°C). Except for this, the zirconia sintered body was produced under the same conditions as in Example 1, and the zirconia sintered body of Comparative Example 1 was obtained. The relative density of the zirconia sintered body of this comparative example was 98.5%, which was not as dense as that of the example. The linear shrinkage rate in this comparative example was 1.5 (% / min).

[0038] Comparative Example 2 The molded body was heated without applying a voltage, and after the temperature was raised to 1200°C, an AC electric field was applied to the molded body at an applied voltage of 60 V / cm. The limiting current was 56 mA / mm 2 A zirconia sintered body was produced in the same manner as in Example 1, except that the energizing current was held for 5 minutes after reaching the limiting current to densify the green body, thereby obtaining a zirconia sintered body of Comparative Example 2. The relative density of the zirconia sintered body of this comparative example was 95%, which was not as dense as that of the example. The linear shrinkage rate of this comparative example was approximately 14 (% / min).

Claims

1. A temperature-raising process in which an AC electric field of 30 V / cm or more and less than 60 V / cm is applied to a zirconia-containing molded body, while the molded body is heated to a temperature (Ta) at which a flash phenomenon can occur in the molded body, and the current flowing through the molded body is 2 mA / mm 2 20mA / mm or more 2 A temperature increasing step (A) of increasing the temperature of the molded body to the temperature (Ta) showing the limiting current value (a) set between: a current increasing step (B) for increasing the current flowing through the compact at the temperature (Ta) after the temperature increasing step (A) from a current value of a starting current, which is the limiting current value (a), to a current value of a densification current, which is a maximum current value flowing through the compact due to a flash phenomenon of the compact, and for increasing the current flowing through the compact while controlling the current value flowing through the compact so that the shrinkage rate of the compact is constant; a densification step (C) of densifying the compact by holding the compact at the temperature (Ta) and under a condition in which a current flowing through the compact exhibits a current value of the densification current after the current increasing step (B); A method for producing a zirconia sintered body comprising the steps of:

2. The method according to claim 1 , wherein in the current increasing step (B), the current flowing through the compact is increased from the current value of the initial current to the current value of the densification current over a period of 5 minutes or more.

3. The current value of the densification current is 80 mA / mm 2 The method for producing a composition according to claim 1 or 2, wherein the composition is a polyolefin.

4. The method according to any one of claims 1 to 3, wherein the temperature (Ta) is 1100°C or less.

5. The method according to any one of claims 1 to 4, wherein the frequency of the AC electric field is 50 Hz or more and 10,000 Hz or less.

6. The method according to any one of claims 1 to 5, wherein the molded body contains 2 mol % to 6 mol % of yttria, with the remainder being zirconia.

Citation Information

Patent Citations

  • Manufacturing method for sintered body and sintered body

    JP2019182689A

  • Fluorescent ceramic producing method and fluorescent ceramic

    JP2020203823A

  • Methods of flash sintering

    US20130085055A1

  • Sintered compact manufacturing method and sintered compact manufacturing device

    WO2021020425A1